Climate-Smart Agricultural Practices in Ghana - Botchway, Vincent Ansah; Sam, Kingsley Odum; Karbo, Naaminong; Essegbey, George Owusu; Nutsukpo, Delali; Agyemang, Kingsley; Zougmoré, Robert B.; Partey, Samuel T. (Council for Scientific and Industrial Research, Ghana, 2016)
The contribution of the agricultural sector to Ghana's economy has been dwindling in relative terms from a high of 39 per cent in 1990s to about 21 per cent in 2014 (ISSER, 2015). This reduction to the sector’s GDP notwithstanding, sector continues to play a major role in the country’s socio-economic growth. However, the sector is threatened by the effects of climate variability and climate change. There are already efforts being made at various levels to address this threat through the adoption and adaption of various technologies and practices. This paper profiles technologies and practices that respond to CSA principles and characteristics in the northern Guinea savannah and Forest agro-ecological zones of Ghana. Two regional workshops were held in Wa and Kumasi for the savannah and forest zones respectively. Over 200 participants consisting of farmers, NGOs, FBOs, MoFA directors and extension workers, traditional rulers, District Chief Executives, Academia and researchers were involved in the technology identification and profiling employing a matrix-ranking tool in the working groups at the various workshops. Participants identified 61 and 21 CSA technologies and practices in the Guinea Savannah and the Forest zones respectively and recommended scaling up of these technologies in the various zones. While the traditional rulers and farmers bemoaned the lack of synergy among the institutions involved in CSA and the lack of policy continuity, policy makers called for strengthening of collaboration between the stakeholders for CSA. The policy and decision makers further called on scientists to make CSA accessible at the farmer level through demonstrations and fact sheets for awareness creation and education and promised to support research and extension with the needed funds. Representatives of Academia and Research on their part pledged solutions that are sustainable and have climate change adaptation and mitigation effects for profit and the well-being of farmers.